Comparison of Ultrasound Guided and Conventional Techniques for Peripheral Venous Catheter Insertion in Pediatric Patients: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Ye, Xiulan; Li, Ming (Frontiers in Pediatrics, 2022)
Background: Ultrasound guided cannulation for peripheral venous insertion is a well-established methodology. However, there has never been a systematic review completed to synthesize evidence within the pediatric population. The current systematic review and meta-analysis was completed to compare the efficacy and safety profile of ultrasound guided peripheral cannulation against the conventional palpation technique within pediatric patients. Methods: A comprehensive search was conducted within the digital databases including Medline, EMBASE, ScienceDirect, Google Scholar and Cochrane library from inception until August 2021. A meta-analysis was then completed with random-effects model and reported pooled risk ratio (RR) or standardized mean difference (SMD) with 95% confidence interval (CI). Results: In total, 9 studies were analysed, which included 1,312 participants, and the majority of studies (5 out 9 studies) were considered high quality. Amongst efficacy outcomes, first attempt success rate had a pooled RR of 1.53 (95% CI: 1.14 to 2.04), overall success rate had a pooled RR of 1.13 (95% CI: 1.01 to 1.26), number of attempts before successful cannulation had a pooled SMD of -1.93 [95%CI: -3.44 to -0.42], time taken for successful cannulation had a pooled SMD of -0.46 [95%CI: -1.20 to 0.28], needle redirections before successful cannulation had a pooled SMD of -1.26 [95%CI: -2.47 to -0.06]. Amongst safety outcomes, venous extravasation had a pooled RR of 1.59 (95% CI: 0.99 to 2.54) and phlebitis had an RR of 0.31 (95% CI: 0.07 to 1.50). Conclusion: Within pediatric patients, ultrasound guided peripheral venous cannulation is more efficacious when compared to the conventional palpation technique.